ChemInform Abstract: Synthesis, Insecticidal and Fungicidal Activities of Methyl 2‐(Methoxyimino)‐2‐(2‐((1‐ (N′‐nitrocarbamimidoyl)‐2‐hydrocarbylidenehydrazinyl)methyl)phenyl) acetates. Issue 28 (June 2016) - Yuan, Xiaoyong; Jia, Changqing; Ma, Yongqiang; Yang, Dongyan; Rui, Changhui; Qin, Zhaohai
Abstract: 23 Title compounds of type (V) or (VIII) are prepared and tested for their insecticidal and fungicidal activities.